2019
DOI: 10.1002/pen.25254
|View full text |Cite
|
Sign up to set email alerts
|

Fracture and Orientation of Long‐Glass‐Fiber‐Reinforced Polypropylene During Injection Molding

Abstract: Injection processing parameters directly influence the final fiber length and may have a negative effect on the mechanical properties of a part. The aim of the work is to investigate and quantify the effects of the injection rate (2/10/50 cm3/s) on the fiber length, the distribution, and orientation during injection molding and the mechanical properties of long‐glass‐fiber‐reinforced polypropylene (LGF/PP) by experimental and simulated methods. When the injection rate increases from 2 to 10 cm3/s, the fiber le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Rohde et al showed that the back pressure has a detrimental effect on both the fiber length and the impact energy absorbance of L-FRP specimens [ 16 ]. Kumar et al investigated the effects of the injection pressure and screw speed on two thermoplastics compounded with different initial fiber lengths [ 17 , 18 , 19 , 20 ]. The results showed that an understanding of the orientation behavior of the fibers in the injection molding process is critical.…”
Section: Introductionmentioning
confidence: 99%
“…Rohde et al showed that the back pressure has a detrimental effect on both the fiber length and the impact energy absorbance of L-FRP specimens [ 16 ]. Kumar et al investigated the effects of the injection pressure and screw speed on two thermoplastics compounded with different initial fiber lengths [ 17 , 18 , 19 , 20 ]. The results showed that an understanding of the orientation behavior of the fibers in the injection molding process is critical.…”
Section: Introductionmentioning
confidence: 99%
“…This specific orientation pattern is well-known and caused by the fountain flow effect. However, the numerical predictions of Hou et al [34] do not match with the empirical orientation in the skin layer. Parveen et al [37] achieved comparable results to Hou et al on a disc geometry (2 mm; 75 mm D) and stated that a higher fiber length leads to a wider core region with more fibers aligned transverse to the flow direction at the end of the flow path.…”
Section: Motivationmentioning
confidence: 93%
“…The results are consistent with Seong et al [33], who noted an increase in Young's modulus, melting temperature, and viscoelastic properties, and a less uniform distribution of the fiber with an increasing fiber length. Hou et al [34] measured a reduction of the average fiber length with an increasing injection rate over the whole length of tensile specimens. Based on the work of Tadmor [35] as well as Osswald and Menges [36], there are seven characteristic regions that can be differentiated in injection molded parts, each with a specific fiber orientation.…”
Section: Motivationmentioning
confidence: 99%
“…Recently, microfibril composites (MFCs) have attracted much attention of many researchers, as the mechanical strength of MFC is typically 30%–50% higher than the calculated values of the rule of mixtures . It is different from traditional filler, such as glass fiber , carbon fiber , and so forth, the reinforced microfibrils in MFC are formed during processing . Therefore, some shortcomings in traditional fiber reinforced composites can be weakened or even be avoided, for example, the wear of processing machinery will be reduced due to the relatively low viscosity of the polymer blends.…”
Section: Introductionmentioning
confidence: 99%